2015
DOI: 10.1016/j.jtcvs.2015.01.038
|View full text |Cite
|
Sign up to set email alerts
|

Survival into adulthood of patients with atrial isomerism undergoing cardiac surgery

Abstract: A significant proportion of patients with isomerism still die before reaching adulthood. Only a fraction of those with obstructed pulmonary veins survive. Having biventricular repair does not confer a survival advantage to those born with right atrial isomerism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 14 publications
3
29
2
Order By: Relevance
“…10 Many patients with isomerism die before reaching adulthood. 11 In 2011, Jacobs and associates 12 reported an analysis of The Society of Thoracic Surgeons congenital heart surgery database of patients with heterotaxy. They found that heterotaxy is a challenging problem with increased discharge mortality in most single ventricle palliation subgroups.…”
Section: Commentmentioning
confidence: 99%
“…10 Many patients with isomerism die before reaching adulthood. 11 In 2011, Jacobs and associates 12 reported an analysis of The Society of Thoracic Surgeons congenital heart surgery database of patients with heterotaxy. They found that heterotaxy is a challenging problem with increased discharge mortality in most single ventricle palliation subgroups.…”
Section: Commentmentioning
confidence: 99%
“…Future studies are required to better understand the pathophysiological mechanisms in this rare subgroup of patients. Though patients with obstructed TAPVD and atrial isomerism are at increased risk of early mortality, 16 it appears that survival after the Fontan completion is associated with a good long-term prognosis.…”
Section: Commentmentioning
confidence: 99%
“…Many previous reports have shown that heterotaxy was associated with increased mortality risk following various palliative procedures including BTS, Norwood, or PAB. [6][7][8][9][10]14,15,[24][25][26] A recent Society of Thoracic Surgeons study examining hospital survival of 1,505 patients with heterotaxy who underwent surgery demonstrated that discharge mortality was higher in patients with heterotaxy compared to patients without heterotaxy for every procedure mortality risk category and for different subgroups of patients such as those who underwent BTS or Fontan. 14 Several recent single institution reports of palliation outcomes in patients with heterotaxy demonstrated increased mortality, respiratory complications, and more complicated postoperative course.…”
Section: Discussionmentioning
confidence: 99%